The Effectiveness of Memorizing Islamic Doctrines as a Prerequisite for Marriage Registration: A Case Study in Teluk Pulai Dalam Village - Yansyah, Muhammad Syafri; Firmansyah, Heri (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This study aims to evaluate the effectiveness of requiring individuals to memorize the obligatory, impossible, and permissible attributes of Allah, along with the pillars of obligatory bathing, as a prerequisite for marriage registration in Teluk Pulai Dalam Village. Despite not being aligned with the provisions of Government Regulation No. 9 of 1975, this practice is widely implemented within the community. This research employs a qualitative subjective approach with an empirical juridical method. Field research was conducted to gather direct insights into the application and impact of memorizing theological and ritual requirements for marriage registration in Teluk Pulai Dalam Village, Kualuh Leidong Subdistrict. Findings indicate that the memorization requirement positively influences the local community. Although it does not comply with formal legal provisions, it enhances individuals’ understanding of Islamic theological principles and the correct procedures for obligatory bathing. As a result, worship practices within the community are perceived as more valid and spiritually meaningful. This study provides a unique perspective on the intersection of religious education and marriage registration practices outside formal state regulations. It highlights how local customs shape religious literacy and compliance with Islamic rituals. The research suggests that integrating religious education into marriage-related practices can strengthen community understanding of Islamic obligations. However, it also raises questions about the legal and administrative alignment of such practices with national regulations. Further studies may explore how similar initiatives can be harmonized with formal legal frameworks.